2022
DOI: 10.3390/cancers14143530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Condom Use after CIN Treatment on Cervical HPV Biomarkers Positivity: Prolonged Follow Up Study

Abstract: Background: Several factors contribute in the cervical healing process following local surgical treatment; in a previous work our group has documented a beneficial mid-term role of regular condom use immediately postoperatively in terms of CIN relapse prevention and expression of active viral biomarkers. Materials and Methods: Aiming to investigate whether the favorable contribution of consistent condom use could be extrapolated in the longer term, we conducted a prospective single center observational study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
1
5
0
1
Order By: Relevance
“…23 Along with HPV 16, HPV 18 and 6, all targeted from vaccination, have been reported as the most common types in cervix and anus of women and men. 24,25 In addition to vaccination, the consistent condom use in women might improve HPV clearance and prognosis, as observed by Valasoulis et al 26 Our data show a high rate of HPV genotypes multiple infections, without significant differences over the years: specifically, every year 37%-43% of patients attending our clinic resulted positive for ≥2 HR types. This could be explained by the fact that HPV types share risk determinants like sexual activity and age, thus multiple infections should be expected.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…23 Along with HPV 16, HPV 18 and 6, all targeted from vaccination, have been reported as the most common types in cervix and anus of women and men. 24,25 In addition to vaccination, the consistent condom use in women might improve HPV clearance and prognosis, as observed by Valasoulis et al 26 Our data show a high rate of HPV genotypes multiple infections, without significant differences over the years: specifically, every year 37%-43% of patients attending our clinic resulted positive for ≥2 HR types. This could be explained by the fact that HPV types share risk determinants like sexual activity and age, thus multiple infections should be expected.…”
Section: Discussionsupporting
confidence: 78%
“…Along with HPV 16, HPV 18 and 6, all targeted from vaccination, have been reported as the most common types in cervix and anus of women and men 24,25 . In addition to vaccination, the consistent condom use in women might improve HPV clearance and prognosis, as observed by Valasoulis et al 26 …”
Section: Discussionmentioning
confidence: 90%
“…A study has shown that consistent condom use after LEEP significantly reduces HPV-positive rates and also appears to significantly reduce rates of CIN recurrence and biomarkers of HPV expression. Additional HPV vaccination administered at the time of treatment could further enhance the positive effects of consistent condom use [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…With comparable clinical accuracy for hrHPV testing in self-samples as clinician-collected material and flexibility for use both in primary cervical screening as well as triage of abnormal samples, advocacy for incorporating self-sampling into organized screening programs is strong, especially after the disruption due to the SARS-CoV-2 pandemic [ 5 , 17 , 20 , 21 , 57 , 58 , 59 , 60 ]. With an ever-growing number of countries considering self-collection for cervical screening, issues to be determined are how to best offer the service, whom to offer it to, adhering to f-u, triage of HPV-positive cases and how to best prepare the public and health systems for this transition [ 14 , 61 ]…”
Section: Discussionmentioning
confidence: 99%